A Compact Multi-band Rectangular Slot Microstrip Antenna for Wi-MAX, WLAN and X-band Applications - R, Banuprakash; S.A, Hariprasad. (International Journal of Engineering and Technology, 2018)
In this paper a rectangular slotted rectangular patch tripple band antenna for wireless applications is presented. The antenna has dimension of about 25 x 20 x 1.6mm3. The antenna operates at the frequencies 3.6 GHz, 5.8 GHz and 7.5 GHz with bandwidth of about 3.61%, 1.03% and 1.07% respectively. This antenna can be used for WIMAX (3.6GHz), WLAN (5.8GHz) and X-band(7.5GHz) applications. The stable radiation pattern, acceptable gain and good impedance matching are observed at obtained frequencies using HFSS tool.Â Â